A assinatura genômica de fungos nos níveis de genes e vias - Aline Soares dos Reis (2021)
Fungi are a monophyletic group of eukaryotic organisms possessing extreme biochemical, physiological and morphological diversity. These organisms play an important ecological role as decomposers and also have major economic importance for the production of beverages, foods, pharmaceuticals, biofuels and other biotechnological processes. On the other hand, several fungi species are also major threats to human health and agriculture as pathogens of humans, other animals and plants. The widespread non-rational usage of antifungal agents is a major concern, as it increasingly selected resistant fungal strains. Another concern is the host toxicity of a considerable fraction of such drugs due to the molecular similarity of host and parasites, as both are closely related eukaryotic organisms. Therefore, fungi are an interesting group to be characterized at the molecular and functional levels for both having a better understanding of the cellular modus operandi of this taxon and also to detect potential new targets for molecular intervention in pathogenic fungi. The Kioto Encyclopedia of Genes and Genomes (KEGG) is a database that provides curated information about groups of homologous genes across species, defined as Kegg Ortholog (KO) groups. KEGG also maps KOs into higher-order layers of biological functions by providing the enzymatic functions of KO groups in different curated biochemical pathways, therefore providing a common layer of genomic components and their functional roles across species. In this work, we used a two-step comparative genomics strategy (gene- and pathway-level) to search for enzymatic roles and biological modules significantly enriched in fungal genomes when compared with other eukaryotic organisms. We used KEGG API to obtain all 535 eukaryotic organisms found in this database as in January 2020, together with their taxonomic classification. We used this information to split these eukaryotic genomes in 129 Fungi (F) and 406 non-Fungi (NF) groups. We also used KEGG API to download the KO groups observed in each eukaryotic genome, as well as their descriptions. To search for KOs significantly enriched in F group, we used the following algorithm: 1) bootstrap genomes in both groups 100 times, obtaining 100 pseudo-replicates of the same size as the original data; 2) for each bootstrap, execute Fisher's exact test, followed by FDR correction, to search for KOs significantly more represented in F when compared to NF; 3) a KO was considered over represented in F if it was found as over represented (q-value < 0.05) in at least 95% of the replicates, and absent in NF group. From the total of 13962 KOs found in at least one eukaryotic genome, we found 495 to be significantly enriched in F group. Among the 50 most abundant KOs, we found clear marks of their ecological roles as decomposers (e.g. K19356 - lytic cellulose monooxygenase (C1-hydroxylating) [EC:1.14.99.54]) and of their metabolic activities of commercial interest (e.g K19305 - NPII; deuterolysin [EC:3.4.24.39]). Interestingly, we also found several enzymes already targeted by antifungal drugs (e.g. K23787 - DMA1_2; E3 ubiquitin-protein ligase DMA1/2 [EC:2.3.2.23] and K19564 - CTR, HNM1; choline transport protein), indicating our strategy also found drug targets already labeled as interesting by other researchers. Finally, we found several interesting candidates for future research that play major roles in fungal lifestyles, such as transcriptional regulators (e.g. K09043 - YAP; AP-1-like transcription factor) and components of cell wall processes (e.g K13682 - BMT, WRY; beta-1,2-mannosyltransferase [EC:2.4.1.-]). To perform a pathway-level comparative genomics analysis, we started by using KEGG API to obtain, for each pathway described in this database, all its KOs. Secondly, we searched all pathways for the enriched KOs in fungal genomes, ranking all pathways by the ratio of the number of enriched KOs in the pathway by the total KO count. Among the 15 pathways containing the largest fractions of enriched fungal KOs, 7 are fungi-specific KEGG pathways (e.g. map04113 - Meiosis - yeast and map04011 - MAPK signaling pathway - yeast). We also found more phylogenetically diverse pathways containing high fractions of KOs enriched in fungal genomes, such as DNA repair (map03450 - Non-homologous end-joining), protein synthesis (map03008 - Ribosome biogenesis in eukaryotes) and fatty acid metabolism (map01040 - Biosynthesis of unsaturated fatty acids), which may comprise interesting targets for a more systemic intervention in fungal biology (e.g search for chokepoints). Together, this work highlights both known drug targets and interesting candidates for future research of fungal biology.